Histomorphological evaluation of skin lesions at the Kadapa Government Medical College teaching institute: A two-year study - Velpula Nagesh Kumar; Shaik Raja Husne Kalam; Polisetty Satya Narayana Rao; Gollapalli Sobha Rani (Golestan University Of Medical Sciences, 2024)
Background: The prevalence of skin diseases varies geographically due to factors, such as etiology, environment, genetics, and lifestyle. The current study aimed to determine the incidence and distribution of skin disorders and to provide a description of the histomorphological spectrum. Methods: This retrospective study was conducted over a period of two years, from June 2021 to May 2023. A total of 202 skin biopsy samples were evaluated. The histopathological examination of the lesions categorized them into eight groups based on the site, pattern of involvement, and cytological features, according to the Lever's Histopathology of the Skin. Group 1 consisted of diseases limited to the epidermis and stratum corneum; group 2 consisted of diseases with localized superficial epidermal or melanocytic proliferation; group 3 consisted of diseases of the superficial cutaneous reactive unit; group 4 included diseases with acantholytic, vesicular, and pustular morphology; group 5 included diseases with perivascular, diffuse, and granulomatous infiltrate of the reticular dermis; group 6 included tumors and cysts of the dermis and subcutis; group 7 consisted of inflammatory disorders of skin appendages; and group 8 consisted of disorders of the subcutis. Results: A total of 202 skin biopsies were collected from individuals aged 8-87 years. The majority of the cases belonged to the age group of 31-40 years. The male-to-female ratio was 1.2:1. The trunk was the most common site of biopsy, accounting for 40% of the cases, followed by the upper limb in 25% of the cases. Histopathological lesions were categorized into eight groups based on the site, pattern, and cytological features. Neoplastic lesions, both benign and malignant, accounted for 10.9% of the cases. The majority of the lesions were related to group 6, accounting for 38.1% of the cases, with the epidermal cyst being the most common lesion (7.92%). Basal cell carcinoma, observed in 2.97% of the cases, was the most common lesion among the neoplastic lesions. Group 5 lesions were the third most common (19.8%), with leprosy accounting for 9.4% of these cases. Conclusion: Histopathological examination of skin biopsies is considered the gold standard for diagnosis, and it is often supported by ancillary techniques. Leprosy was the most common disease identified in this study, which underscores the importance of effective preventive measures for control.